The Political Determinants of Inward FDI - Triarchi, Eirini; Marangos, John (Panoeconomicus, 2024)
The popularity of Foreign Direct Investment (FDI) stimulates research on its determinants. This paper highlights the importance of political determinants in explaining inward FDI variation across countries. Adopting the argument that no single theory exists for FDI, it identifies the political factors based on the results of related empirical studies. The literature review’s primary concern is to provide underpinnings for further research on inward FDI distribution in the contemporary international political scene. It sets up the theoretical links between political regimes, political determinants, and FDI. The paper focuses on the importance of specific political variables established in all political systems to influence foreign investors’ decision-making process. The distinguished determinants are property rights protection, the signing of Bilateral Investment Treaties (BITs), human rights, and quality of governance. JEL: F21, F23, F53, P14, P16.